Peran Leader-Member Exchange (LMX) dan Occupational Stress untuk Memprediksi Intensi Turnover - Ramadhan Ulfah Widyaningsih; Ridwan Saptoto (Gadjah Mada Journal of Psychology (GamaJoP), 2019)
The aim of this study was to examine the effect of leader-member exchange (LMX) and occupational stress on the turnover intention on PT. Komatsu Indonesia’s employees. It was hypothesized that leader-member exchange (LMX) and occupational stress predict turnover intention together. The subjects of this study were 66 employees of PT. Komatsu Indonesia that had been working for at least 3 years. The data were obtained using the turnover intention scale, LMX-MDM (Leader-Member Exchange-Multidimensional Dimension Measure) scale, and SDS (Stress Diagnostic Survey) scale. The data were analyzed using multiple linear regression. Results showed that occupational stress significantly predicts turnover intention. The hypothesis was rejected because leader-member exchange (LMX) and occupational stress didn’t predict turnover intention together. The significance level of occupational stress’s effect on turnover intention is 0.044 (p<0.05) and it explained 7.2% of turnover intention. Findings does not support the role of LMX and occupational stress in predicting turn over intention.